Football hooliganism in the countries of the Visegrád Group: cooperation and confrontation - Smolík, Josef (Kultura-Społeczeństwo-Edukacja, 2019)
The article deals with the description of football hooligans in the countries of Visegrad Group (Czech Republic, Slovakia, Poland, Hungary). Text describes history of this phenomenon in the central Europe in the context of European Football Championships of 2012 and 2016. Particular hooligans’ groups, the basic characteristics, relations and manifestations of these groups are briefly presented. In the final part there are outlined particular actors participating in tackling with football hooligans, including legislative procedures stemming from European Convention. In the conclusion itself there is discussed also police’ cooperation during big football championships.